Numerical simulation study on mechanical properties of rock like specimen with cracks under the coupling of loading and unloading and osmotic pressure - Liangxiao Xiong; Haijun Chen; Zhongyuan Xu; Deye Hu (Archives of Civil Engineering, 2024)
The saturated metasandstone is taken as the research object, and the uniaxial compression characteristics of the saturated metasandstone are simulated by means of the artificially made saturated sandstone samples. By checking the parameters of the Particle Flow Code (PFC) numerical simulation of loading and unloading seepage stress coupling, the effects of the conductivity coefficient, the pipe diameter, the apparent volume of the domain and the time step on the calculation results are analyzed. When PFC is used for numerical simulation of seepage stress coupling, the conductivity coefficient K can be taken as 0.010. When the pipe diameter is 1.0 mm, the apparent volume of the current domain is 1 x 10–6 m3, the water pressure distribution inside the sample is relatively uniform. The influence of time step on the compressive strength and peak strain of the specimen can be almost ignored. Under the action of water pressure, the compressive strength of the intact rock like sample and the rock like sample with cracks decreases, and the compressive strength of the sample decreases gradually with the increase of water pressure. When the inclined angle of fracture is the same, the seepage pressure is the same, and the confining pressure is the same, the compressive strength of the specimen also increases with the increase of the initial axial stress level during unloading. When the confining pressure and the osmotic pressure are the same, the unloading effect makes the crack development of the specimen faster and more complete, the specimen is more fragmented and multiple parallel shear bands develop.